2013
DOI: 10.1080/09603107.2012.707770
|View full text |Cite
|
Sign up to set email alerts
|

Are commodity markets characterized by herd behaviour?

Abstract: Twenty years ago, Pindyck and Rotemberg concluded that commodity prices exhibited excessive co-movements and that commodity markets were characterized by herd behaviour. The herding hypothesis has recently experienced a revival. A number of studies have concluded that commodities have become 'financialized' and contaminated by the stock market because of the large influx of hedge funds, index trackers and financial investors. Analysing monthly prices of 20 commodities for the period 1986-2010, we find that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…Similarly, Boyd, Buyuksahin, Haigh, and Harris (2009) examine trading data and find that herding among hedge funds does not destabilize the crude oil market. More recently, Steen and Gjolberg (2013) examine the correlation patterns and principal components describing commodity returns and find no significant support for herd behavior.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Similarly, Boyd, Buyuksahin, Haigh, and Harris (2009) examine trading data and find that herding among hedge funds does not destabilize the crude oil market. More recently, Steen and Gjolberg (2013) examine the correlation patterns and principal components describing commodity returns and find no significant support for herd behavior.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In the latter paper, they found that skewness and kurtosis have not changed significantly either. In another paper, Steen and Gjøberg (2013) found no support for commodities having turned into "one" asset.…”
Section: Introduction and Literature Reviewmentioning
confidence: 95%
“…The authors argue that owing to the passive and long-only nature of commodity index investments, these are unlikely culprits of inflated commodity prices. Steen and Gjølberg (2013) There is also a growing body of literature that addresses the issue of increasing commodity market volatility. McPhail et al (2012) study corn futures traded on the Chicago Board of Trade and use a structural vector autoregressive model and variance 310 decomposition to analyse corn price volatility.…”
Section: The Role Of Speculationmentioning
confidence: 99%